Given integral $(1)$

$$\int_{-\infty}^{+\infty}{\mathrm dx\over x^2}\cdot\left(2-{\sin x\over \sin\left({x\over 2}\right)}\right)^{n+1}={2n\choose n}\pi\tag1$$ Where $n\ge0$

How does one prove $(1)$?

An attempt:

Recall $$\sin(2x)=2\sin x\cos x$$

$(1)$ becomes

$$2^{n+1}\int_{-\infty}^{+\infty}{\mathrm dx\over x^2}\cdot\left(1-\cos\left({x\over 2}\right)\right)^{n+1}\tag2$$

Applying binomial series to $(2)$, then we have

$$2^{n+1}\sum_{k=0}^{n+1}(-1)^k{n+1\choose k}\int_{-\infty}^{+\infty}{\mathrm dx\over x^2}\cdot\cos^k\left({x\over 2}\right)\tag3$$

Not sure how to proceed...

  • $\begingroup$ Have you had a lecture on complex analysis ? $\endgroup$
    – Jean Marie
    Mar 26 '17 at 20:31

I will first prove that if $f(x)$ is a continuous and $\pi$-periodic function on $\mathbb{R}$, then $$\int_{-\infty}^{\infty} f(x) \, \frac{\sin^{2}(x)}{x^{2}} \, dx = \int_{0}^{\pi} f(x) \, dx$$ provided that both integrals converge.

We will need that fact that $$\sum_{n=-\infty}^{\infty} \frac{1}{(z+n \pi)^{2}} = \csc^{2}(z).$$

(See THIS QUESTION for a derivation.)

$$\begin{align} \int_{-\infty}^{\infty} f(x) \, \frac{\sin^{2}(x)}{x^{2}} \, dx &= \sum_{n=-\infty}^{\infty} \int_{n \pi}^{(n+1) \pi} f(x) \frac{\sin^{2}(x)}{x} \, dx \\ &= \sum_{n = -\infty}^{\infty} \int_{0}^{\pi} f(u+ n \pi) \, \frac{\sin^{2}(u + n \pi)}{(u + n \pi)^{2}} \, du \\ &= \sum_{n=-\infty}^{\infty} \int_{0}^{\pi} f(u) \, \frac{\sin^{2}(u)}{(u + n \pi)^{2}} \, du \\ &= \int_{0}^{\pi} f(u) \sin^{2}(u) \sum_{n=\infty}^{\infty} \frac{1}{(u+n \pi)^{2}} \, du \\ &= \int_{0}^{\pi} f(u) \, du \end{align}$$

Jack D'Aurizio already showed that the integral is equivalent to $$I(n) = 2^{2n} \int_{-\infty}^{\infty} \frac{\sin^{2n+2}(x)}{x^{2}} \, dx. $$

So using the above formula, we get $$\begin{align} I(n) &= 2^{2n} \int_{0}^{\infty} \sin^{2n}(x) \frac{\sin^{2}(x)}{x^{2}} \, dx = 2^{2n}\int_{0}^{\pi} \sin^{2n}(x) \, dx \\ &= 2^{2n+1} \int_{0}^{\pi/2} \sin^{2n}(x) \, dx = 2^{2n+1} \frac{1}{2^{2n}} \binom{2n}{n} \frac{\pi}{2} \tag{1}\\&= \binom{2n}{n} \pi . \end{align}$$

$(1)$ Wallis's integral


The given integral equals $$ I(n) = 2^{n+1}\int_{\mathbb{R}}\frac{(1-\cos(x/2))^{n+1}}{x^2}\,dx = 2^n\int_{\mathbb{R}}\frac{(1-\cos z)^{n+1}}{z^2}\,dz \tag{1}$$ or: $$ I(n) = 2^{2n+2}\int_{0}^{+\infty}\frac{\sin^{2n+2}(z/2)}{z^2}\,dz = 4^n\int_{\mathbb{R}}\frac{\sin^{2n+2}(z)}{z^2}\,dz \tag{2} $$ that can be computed through the Fourier cosine series of $\sin^{2n+2}(z)$, since $$ \int_{\mathbb{R}}\frac{1-\cos(mx)}{x^2}\,dx = m\pi.\tag{3}$$ In particular, since $\sin(z)=\frac{e^{iz}-e^{-iz}}{2i}$, $$ \sin^{2n+2}(z) = \frac{1}{(2i)^{2n+2}}\sum_{k=0}^{2n+2}\binom{2n+2}{k}\exp\left((2k-2n-2)iz\right)(-1)^{k} \tag{4}$$ equals: $$ \frac{1}{(2i)^{2n+2}}\sum_{k=1}^{n+1}\binom{2n+2}{n+1+k}\left(1-\cos(kz)\right)(-1)^k \tag{5} $$ and the problem boils down to the computation of the combinatorial sum $$ \sum_{k=1}^{n+1}\binom{2n+2}{n+1+k}k(-1)^k \tag{6}$$ that is pretty simple. As an alternative, once we reach $(2)$ we may directly invoke Lagrange's inversion theorem and Cauchy's integral formula to derive that the answer is directly related with the coefficients of the Taylor series of $\arcsin(z)$ at the origin.


In this solution I will use the Fourier transform \begin{equation*} \hat{f}(\xi) = \int_{-\infty}^{\infty}e^{-i\xi x}f(x)\, dx. \end{equation*} It is well known that if $f(x) = \dfrac{\sin^2(x)}{x^2}$ then $\hat{f}(\xi) = \pi\left(1-\frac{|\xi|}{2}\right)$ if $|\xi|<2$ and $0$ otherwise. Via $1-\cos\left(\frac{x}{2}\right) = 2\sin^2(\frac{x}{4})$, the substitution $x:=4x$ and the Euler formula $\sin(x) = \frac{1}{2i}(e^{ix}-e^{-ix})$ I can proceed from Bui's formula (3). \begin{gather*} I = 2^{n+1}\int_{-\infty}^{\infty}\dfrac{1}{x^2}\left(1-\cos\left(\frac{x}{2}\right)\right)^{n+1}\, dx = 4^{n}\int_{-\infty}^{\infty}\dfrac{\sin^{2}(x)}{x^2}\sin^{2n}(x)\, dx =\\[2ex] \int_{-\infty}^{\infty}\dfrac{\sin^{2}(x)}{x^2}(-1)^{n}\left(e^{ix}-e^{-ix}\right)^{2n}\, dx. \end{gather*} But (cf. Jack D'Aurizio) \begin{equation*} \left(e^{ix}-e^{-ix}\right)^{2n}= \sum_{k=0}^{2n}\binom{2n}{k}(-1)^{2n-k}e^{-i(2n-2k)x} = \sum_{k=-n}^{n}\binom{2n}{n-k}(-1)^{n+k}e^{-i2kx}. \end{equation*} Thus \begin{gather*} I = \sum_{k=-n}^{n}\binom{2n}{n-k}(-1)^{2n+k}\int_{-\infty}^{\infty}\dfrac{\sin^{2}(x)}{x^2}e^{-i2kx}\, dx = \sum_{k=-n}^{n}\binom{2n}{n-k}(-1)^{2n+k}\hat{f}(2k) = \\[2ex] \binom{2n}{n}\hat{f}(0) = \pi\binom{2n}{n}. \end{gather*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.